Multi-Criteria Decision Making Application in the Education Context (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2018)
Business schools are confronted with a challenge of developing students to be managers, focused on productivity and adding value at the work process. 21st century education should aid student population substantially in thinking beyond profitability and self-interest and lead their strategical thinking process towards sustainable development. Our aim is to help the teaching staff in business education by providing them the tools to understand their students’ decision-making process and preferences. The goal of the study is to investigate if modern technologies support responsible decision making of students. A quantitative study was carried. The tool used was Super Decisions Software. Our results show that technology, even though a potentially useful tool in the responsible decision-making process needs integration into the appropriate business models. The sample of students’ behaviours in decision-making process can also be identified as responsible.This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.